2023
DOI: 10.1002/advs.202206938
|View full text |Cite
|
Sign up to set email alerts
|

Elevated PDGF‐BB from Bone Impairs Hippocampal Vasculature by Inducing PDGFRβ Shedding from Pericytes

Abstract: Evidence suggests a unique association between bone aging and neurodegenerative/cerebrovascular disorders. However, the mechanisms underlying bone-brain interplay remain elusive. Here platelet-derived growth factor-BB (PDGF-BB) produced by preosteoclasts in bone is reported to promote age-associated hippocampal vascular impairment. Aberrantly elevated circulating PDGF-BB in aged mice and high-fat diet (HFD)-challenged mice correlates with capillary reduction, pericyte loss, and increased blood-brain barrier (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 107 publications
2
31
1
Order By: Relevance
“…Second, our study focused on the effect of NSCs on TJPs in the BBB. Other microvascular structural components, such as astrocytic end-feet and pericytes, are also pertinent to BBB integrity and may be impacted by NSCs treatment 50 . Third, there are several alternative mechanisms by which NSCs could impact BBB permeability that were not explored, including via antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our study focused on the effect of NSCs on TJPs in the BBB. Other microvascular structural components, such as astrocytic end-feet and pericytes, are also pertinent to BBB integrity and may be impacted by NSCs treatment 50 . Third, there are several alternative mechanisms by which NSCs could impact BBB permeability that were not explored, including via antioxidative effects.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 conditional Pdgfb knockout (pdgfb cKO ) and Pdgfb transgenic male mice (pdgfb cTG ) were generated as previously described [ 6 , 7 , 26 ]. Briefly, Pdgfb f/f mouse strain was purchased from Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that metabolic stress, especially high-fat diet (HFD) challenge, exacerbates neuroinflammation and cognitive decline [ 3 5 ]. Our previous work also demonstrated that HFD promotes preosteoclast senescence and platelet-derived growth factor-BB (PDGF-BB) secretion into the circulation, which is one of the cause for microvascular impairment [ 6 , 7 ]. However, how PDGF-BB secretion induced by HFD challenge impairs brain function and the mechanism of the bone-brain axis participation in metabolic stress-induced brain vascular impairment remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standardized set of bone/bone marrow senescence/SASP-associated factors and genes, named SenMayo [57], has been recently formulated to inform about the specificity of senescencerelated factors and their applicability across tissues and species for senotherapeutic therapies. For instance, the secretion of platelet-derived growth factor-BB by senescent [58] preosteoclasts manifests as a systemic pro-aging factor, contributing to the age-associated increase in arterial stiffness and cerebrovascular impairment [59].…”
Section: The Musculoskeletal Systemmentioning
confidence: 99%